Účinnost převedení žen po menopauze s časným hormonálně dependentním karcinomem prsu z adjuvantního tamoxifenu na anastrozol: metaanalýza - Jonat, Walter; Gnant, Michael; Boccardo, Francesco; Kaufmann, Manfred; Rubagotti, Alessandra; Zuna, Ivan; Greenwood, Mike; Jakesz, Raimund; Janda, Vratislav (The lancet oncology CZ, 2007)
For more than 20 years, tamoxifen has been the mainstay of adjuvant endocrine therapy for women with hormone-sensitive early-stage breast cancer. However, not only does tamoxifen have potential side-effects such as an increased risk of endometrial cancer and thromboembolic events, but patients can also develop resistance to the drug. We aimed to investigate whether switching treatment of postmenopausal women with such breast cancer to anastrozole after 2-3 years of tamoxifen would be more effective than continuing on tamoxifen for a total of 5 years. METHODS: We did a meta-analysis of three clinical trials--the Austrian Breast and Colorectal Cancer Study Group (ABCSG 8), Arimidex-Nolvadex (ARNO 95), and the Italian Tamoxifen Anastrozole (ITA) studies--in which postmenopausal women with histologically confirmed, hormone-sensitive early-stage breast cancer were randomised to 1 mg/day anastrozole (n=2009) after 2-3 years of tamoxifen treatment or to continued 20 or 30 mg/day tamoxifen (n=1997). We analysed the data with a stratified Cox proportional hazards model with the covariates of age, tumour size, nodal status, grade, surgery, and chemotherapy. FINDINGS: Patients who switched to anastrozole had fewer disease recurrences (92 vs 159) and deaths (66 vs 90) than did those who remained on tamoxifen, resulting in significant improvements in disease-free survival (hazard ratio 0.59 [95% CI 0.48-0.74]; p<0.0001), event-free survival (0.55 [0.42-0.71]; p<0.0001), distant recurrence-free survival (0.61 [0.45-0.83]; p=0.002), and overall survival (0.71 [0.52-0.98]; p=0.04). INTERPRETATION: Our results show that the clinical benefits in terms of event-free survival seen in individual trials for those patients who switched to anastrozole translate into a benefit in overall survival. These findings confirm that clinicians should consider switching postmenopausal women who have taken adjuvant tamoxifen for 2-3 years to anastrozole.
Keywords: Tamoxifen; Randomized Controlled Trials as Topic; Postmenopause; hormonální protinádorové látky; Triazoles; nádory prsu; přežití bez známek nemoci; Disease-Free Survival; Humans; Receptors, Estrogen; postmenopauza; Breast Neoplasms; Nitriles; Antineoplastic Agents, Hormonal; Disease Progression; tamoxifen; randomizované kontrolované studie jako téma; ženské pohlaví; nitrily; receptory pro estrogeny; lidé; triazoly; progrese nemoci; Female